Чебишовське наближення раціональним виразом із точним відтворенням значення функції та її похідних у заданих точках - Малачівський, П.С. (Видавничий дім "Академперіодика" НАН України, 2008)
The problem of Chebyshev (uniform) approximation of a discrete function by a rational expression with Hermite interpolation is considered. The characteristic property of a Chebyshev approximation with exact reproduction of a function and its derivatives to the r order at given points is established. A Remez algorithm to determine the parameters of this approximation is proposed.